STRATEGIC PLAN FOR RETAILERS BEFORE THE ECONOMIC CRISIS CAUSED BY THE COVID-19 PANDEMIC - Gabriel Díaz Jiménez, Juan; Natalia Feltes Dávalos, María; Noemi Feltes Rodas, Priscila (Revista Gênero e Interdisciplinaridade, 2023)
The current crisis caused by COVID-19 caused companies to interrupt their commercial activities, generating an abrupt economic slowdown. This situation has taken the world by surprise and workers in all areas were the most vulnerable to being affected by the pandemic crisis, leading to layoffs or temporary suspensions of their work activities, due to the difficult situation faced by companies. The main objective of this research was to plan business strategies that help the merchants of the CDE Jebai Center gallery in the face of the economic crisis caused by the COVID-19 pandemic. The interview technique was applied through a questionnaire with open questions to a number of 25 companies from the Jebai Center gallery in Ciudad del Este. This research was developed under the paradigm of the qualitative approach and the level was explanatory. With the results of the data collection instruments, it was possible to understand that this crisis has generated great losses, mainly in economic and personal terms. Many companies applied strategies related to online sales through social networks, which was quite effective in avoiding the total closure of their businesses.